(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The story of Augustus Pullman pulls every reader to cherish the warmth that family and friends provide to build him into a competent individual with a confident identity. In the process of building his individuality cum identity, he learns to observe the individuality of his close family members and dear friends. As the entire narrative centres on love in many forms, not only Augustus, but also his loved ones are capable of sculpting their individuality and embracing it. The researcher aims to take a closer look at the process by which Augustus and his sister, Olivia work on their individualities in correspondence with the relationship they share between them as special siblings. In order to carry out a credible unbiased analysis, the researcher opts to employ the Separation-Individuation theory of Margaret S. Mahler to find out how their ego has played a significant role to shape their identities. The findings are unravelled in this research article.